2006
DOI: 10.1080/08035250600589033
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of unwanted and unlawful sexual experiences reported by Danish adolescents: Results from a national youth survey in 2002

Abstract: A relatively high percentage of Danish adolescents have early, unlawful sexual experiences. However, young people's own perception of sexual abuse tends to differ from that of the authorities, or their tolerance of abusive incidents is high. Gender differences were found in factors predicting perception of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
9
29
2
1
Order By: Relevance
“…This said, the high prevalence of CSA should be interpreted within the context of our definition of CSA, because the most commonly reported form was CSA without physical contact, whereas CSA with penetration was least common, reported by only 2.5% of girls and 0.6% of boys. These findings are consistent with literature reports that CSA is two to four times more prevalent among girls [1,13,19]. Child sexual abuse without physical contact happened most frequently at home or in cyberspace, and perpetrators were most often strangers.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This said, the high prevalence of CSA should be interpreted within the context of our definition of CSA, because the most commonly reported form was CSA without physical contact, whereas CSA with penetration was least common, reported by only 2.5% of girls and 0.6% of boys. These findings are consistent with literature reports that CSA is two to four times more prevalent among girls [1,13,19]. Child sexual abuse without physical contact happened most frequently at home or in cyberspace, and perpetrators were most often strangers.…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, one half to three quarters of victims reported that they had been molested by juveniles, and only 0% -10.7% of victims reported family members as perpetrators, depending on the type of CSA and the victim's gender. Consistent with previous literature [13,19,24]., predictors of CSA were being female, not living with both biological parents, and having parents with a lower education level or of non-Swiss nationality.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations